INFLUENCE OF SOCIAL MEDIA LANGUAGE ON WRITTEN-ENGLISH OF NCE STUDENTS IN KWARA STATE COLLEGE OF EDUCATION ILORIN - Thompson Toryuha Aun; Ridwannullahi Kolapo Oniye; Timothy Opeyemi Yayi (SocioEdu: Sociological Education, 2024)
As the world advances, everything, including the way we communicate and relate to people and students have also taken these changes they are familiar and used to into schools that it affects their written English. The study examined influence of social media language on written English of students in Kwara State College of Education, Ilorin. Descriptive survey was used for the study where multistage sampling techniques of purposive and simple random sampling were used to select respondents. Researcher designed questionnaire was used to garner data from 399 respondents while descriptive statistics of percentage, mean and t-test were used for research questions and testing of hypotheses. The study revealed among others that students use several social media sites and students are influenced by social media regardless of gender or course combination. The study recommended that sensitization and monitoring on the use of social media should be carried out among the students.